Novel Inhibitory Actions of Neuroactive Steroid [3α,5α]-3-Hydroxypregnan-20-One on Toll-like Receptor 4-Dependent Neuroimmune Signaling - Alejandro G. Lopez; Venkat R. Chirasani; Irina Balan; Todd K. O’Buckley; Makayla R. Adelman; A. Leslie Morrow (Biomolecules)
The endogenous neurosteroid (3α,5α)-3-hydroxypregnan-20-one (3α,5α-THP) modulates inflammatory and neuroinflammatory signaling through toll-like receptors (TLRs) in human and mouse macrophages, human blood cells and alcohol-preferring (P) rat brains. Although it is recognized that 3α,5α-THP inhibits TLR4 activation by blocking interactions with MD2 and MyD88, the comprehensive molecular mechanisms remain to be elucidated. This study explores additional TLR4 activation sites, including TIRAP binding to MyD88, which is pivotal for MyD88 myddosome formation, as well as LPS interactions with the TLR4:MD2 complex. Both male and female P rats (n = 8/group) received intraperitoneal administration of 3α,5α-THP (15 mg/kg; 30 min) or a vehicle control, and their hippocampi were analyzed using immunoprecipitation and immunoblotting techniques. 3α,5α-THP significantly reduces the levels of inflammatory mediators IL-1β and HMGB1, confirming its anti-inflammatory actions. We found that MyD88 binds to TLR4, IRAK4, IRAK1, and TIRAP. Notably, 3α,5α-THP significantly reduces MyD88-TIRAP binding (Males: −31 ± 9%, t-test, p < 0.005; Females: −53 ± 15%, t-test, p < 0.005), without altering MyD88 interactions with IRAK4 or IRAK1, or the baseline expression of these proteins. Additionally, molecular docking and molecular dynamic analysis revealed 3α,5α-THP binding sites on the TLR4:MD2 complex, targeting a hydrophobic pocket of MD2 usually occupied by Lipid A of LPS. Surface plasmon resonance (SPR) assays validated that 3α,5α-THP disrupts MD2 binding of Lipid A (Kd = 4.36 ± 5.7 μM) with an inhibition constant (Ki) of 4.5 ± 1.65 nM. These findings indicate that 3α,5α-THP inhibition of inflammatory mediator production involves blocking critical protein-lipid and protein-protein interactions at key sites of TLR4 activation, shedding light on its mechanisms of action and underscoring its therapeutic potential against TLR4-driven inflammation.